Az illír mozgalom magyar kötődései – horvát szemmel I. - Lukács, István; Kálecz-Simon, Orsolya (Slavia Centralis, 2020)
Hungarian affiliations of the Illyrian movement – from Croatian perspective I.The article gives a historical overview of the Croatian scientific interpretation of Hungarian contacts and spiritual-political patterns in the development of the Croatian Illyrian movement. The first part of the study presents basic modern theoretical views on the reconstruction of historical narratives, while the second part highlights Croatian scientific achievements in the research of the pre-Illyrian period. The importance of the Jacobin movement and the Freemasons in the emergence of the Illyrian movement is emphasised. The bishop of Zagreb, Maksimilijan Vrhovec, played an important role in the pre-Illyrian period with his new initiatives. A special chapter of the article is dedicated to his work and the presentation of his Hungarian contacts. Another special chapter is dedicated to the extremely rich oeuvre of the leader of the movement, Ljudevit Gaj, and his contacts with the Hungarians. The formation of Slavic and Croatian historical consciousness of Ljudevit Gaj was strongly influenced by the most respected Hungarian historian of the era, István Horvát. Horvát’s romantic megalomaniac lectures on the origin of the Hungarians attracted Gaj’s attention during the time he spent studying in Pest.
Keywords: historical narrative; Illyrian movement; Croatian-Hungarian spiritual contacts